2022
DOI: 10.1111/jen.13014
|View full text |Cite
|
Sign up to set email alerts
|

4‐allylanisole as a lure adjuvant for Dendroctonus frontalis (Coleoptera: Curculionidae: Scolytinae) and two associated beetles

Abstract: The southern pine beetle, Dendroctonus frontalis Zimmermann (Coleoptera: Curculionidae: Scolytinae), is a major pine tree killer in North and Central America. In the southeastern USA, responses by D. frontalis to its aggregation pheromone can be substantially increased by at least three host odours: the monoterpenes alpha‐ and beta‐pinene, and the phenylpropanoid 4‐allylanisole. We executed three trapping experiments to assess the influence of 4‐allylanisole release rate on aggregation behaviour of D. frontali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Given the spread of SPB further north [23], out of the southeastern United States, other regions will need to begin a means of assessing their presence and impacts on forested areas [7]. This could be a combination of field-based monitoring/trapping [6] and remotely sensed techniques like that covered here and with other sensors. Future research should consider forest density relationships with changes in spectral reflectance, particularly infrared portions of the spectrum commonly associated with healthy vegetation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the spread of SPB further north [23], out of the southeastern United States, other regions will need to begin a means of assessing their presence and impacts on forested areas [7]. This could be a combination of field-based monitoring/trapping [6] and remotely sensed techniques like that covered here and with other sensors. Future research should consider forest density relationships with changes in spectral reflectance, particularly infrared portions of the spectrum commonly associated with healthy vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…Insect monitoring and detection efforts help to determine counts and insect sex ratios that may preclude an outbreak [6,7]. Once started, SPB outbreaks can be difficult to manage.…”
Section: Introductionmentioning
confidence: 99%
“…(+)-alpha-Pinene enhances attraction more than the (−)-enantiomer, but not more than the racemate [246]. A minor constituent of the resin of host pines for D. frontalis, 4-allylanisole, increased attraction to a pheromone component combination (frontalin and exoand endo-brevicomin) in a positive dose-dependent manner when released at approximately 5 to 500 mg/d (causing up to a 50-fold catch increase), with or without alpha-pinene also present [165]. These results contrast with some studies which have reported 4-allylanisole to have repellant and attraction-inhibiting activity [257,258].…”
Section: Dendroctonus Frontalis Zimmermann-southern Pine Beetlementioning
confidence: 95%
“…Two oxygenated monoterpenes without a known natural origin relevant to D. terebrans biology, 1,4-cineole and eucalyptol, increased attraction to the bicyclic ketal combination with or without alpha-pinene also present [244]. 4-Allylanisole released from approximately 5 to 500 mg/d enhanced attraction to the combination of the ternary bicyclic ketal combination and alpha-pinene in a positive dose-dependent manner [165].…”
Section: Dendroctonus Terebrans (Olivier)-black Turpentine Beetlementioning
confidence: 98%
See 1 more Smart Citation